Pengaruh Terapi Bermain terhadap Tingkat Sosialisasi Anak Tuna Grahita SLB Negeri Selong - Muratama, Muhammad Satriadi; Setiawati, Farida Agus (Jurnal Penelitian Kesejahteraan Sosial, 2020)
The purpose of this study was to determine the effect of play therapy on the level of socialization of children with mild adolescence. This research is pre-experimental design research, one group pre-test-post-test. The number of samples in this study was 40 students. The sampling technique was done randomly with a total sampling technique. The results of the Wilcoxon Signed Rank Test with an error rate (Î±) = 0.05 obtained a value of p = 0,000 (p <Î±) so that it can be concluded that there is an influence of play therapy on the level of socialization of children with Mild Grump at Selong State SLB.